2013
DOI: 10.5114/aoms.2013.38687
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is elevated in patients with patent foramen ovale

Abstract: IntroductionPlatelets play a major role in thromboembolic events. Increased mean platelet volume (MPV) indicates higher platelet reactivity and also a tendency to thrombosis. Patent foramen ovale (PFO), persistence of the fetal anatomic shunt between right and left atria, is strongly associated with cryptogenic stroke. The aim of this study is to determine the relationship between MPV and PFO and if such an association exists, whether higher MPV levels may require antiplatelet therapy before a thromboembolic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…[10][11][12] Furthermore, the mean platelet volume was asserted to be greater in PFO cases. 13,14 In addition, the prevalence of deep venous thrombosis was also stated to be elevated in PFO and CS patients. 15 Moreover, pelvic vein thrombosis was noted to be more common in CS patients in Paradoxical Emboli from Large Veins in Ischemic Stroke (PELVIS) trial.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12] Furthermore, the mean platelet volume was asserted to be greater in PFO cases. 13,14 In addition, the prevalence of deep venous thrombosis was also stated to be elevated in PFO and CS patients. 15 Moreover, pelvic vein thrombosis was noted to be more common in CS patients in Paradoxical Emboli from Large Veins in Ischemic Stroke (PELVIS) trial.…”
Section: Discussionmentioning
confidence: 94%
“…21,22 Furthermore, an increase in the MPV has also been observed in conditions like patent foramen ovale, myocardial infarction, and cerebral infarction. [23][24][25] Therefore, increased MPV values have been considered a vascular risk factor. This current study found no significant difference between the two study groups with respect to platelet count and there was no correlation between MPV and platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters such as the morphology of PFO, presence of septal aneurysm, and deep venous thrombosis are sought before PFO closure to reduce recurrent stroke risk [5,6]. Inflammation is related with an increased risk of thrombosis [13,19]. To date, the association between NLR and PLR, which are markers of inflammation, atherosclerosis, and stroke, have not been evaluated in patients with PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the neutrophil to lymphocyte ratio (NLR) is suggested as an inflammation marker of stroke [12]. Similarly, platelet activation contributes to the inflammation, and consequently relative thrombocytosis and initiation and progression of atherosclerosis [12,13]. Recent studies have demonstrated higher platelet to lymphocyte (PLR) values in patients with stroke [14].…”
Section: Introductionmentioning
confidence: 99%